2019
DOI: 10.7189/jogh.09.020417
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the prevalence of common mental disorders in people with non-communicable diseases in Bangladesh, India, and Pakistan

Abstract: BackgroundThe prevalence of mental and physical comorbidities is unknown in South Asia, as estimates of mental ill health in patients with non-communicable diseases (NCDs) have predominantly come from studies based in the United States, Europe and Australasia. This systematic review and meta-analysis summarises evidence and provides pooled estimates of the prevalence of common mental disorders in adults with non-communicable diseases in South Asia.MethodsWe included prevalence studies of depression and anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
0
28
1
2
Order By: Relevance
“…In view of the rapid spread of COVID-19 and the increase in the number of cases in Pakistan, it is necessary to have a clear picture of the state of public awareness and their practices in the context of the precautionary measures. In addition, Pakistan is a populous country and is facing enormous pressure on non-communicable diseases [17]. Both of these factors increase the country's vulnerability to this deadly infection and results in higher mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the rapid spread of COVID-19 and the increase in the number of cases in Pakistan, it is necessary to have a clear picture of the state of public awareness and their practices in the context of the precautionary measures. In addition, Pakistan is a populous country and is facing enormous pressure on non-communicable diseases [17]. Both of these factors increase the country's vulnerability to this deadly infection and results in higher mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological studies have enabled good estimates of the prevalence of mental illness and co‐morbidities in the country (Gautham et al, 2020; Uphoff et al, 2019). The National Mental Health Survey (NMHS) 2016 demonstrated a 13.7% lifetime prevalence and 10.6% point prevalence of mental illness (National Mental Health Survey of India , 2015‐16 , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of depression is two to three times higher in people with an NCD [11,12]. A recent systematic review of hospital-based studies in South Asia, revealed a pooled estimate of depression of 40% in patients with diabetes, 37% for patients with cancer, 38% in patients with hypertension, 39% in patients with stroke, and 44% in patients with chronic obstructive pulmonary disease [13]. This co-morbidity of depression with an NCD is important because it worsens the outcomes for both and is associated with poorer self-management and treatment adherence, reduced treatment response and higher morbidity and mortality for both [14,15].…”
Section: Introductionmentioning
confidence: 99%